Determinants of hormonal contraceptive use and its effects among married women of reproductive age group in Kathmandu, Nepal - Shrestha, Supri Raj; Silvanus, Vinutha; Shakya, Bharati (Nepal Medical College Journal, 2022)
The prevention of unwanted pregnancy, unsafe abortion and maternal mortality remains an important part of the practice of medicine. Several forms of hormonal contraception have been used to control female fertility. These are associated with benefits and risk. The current study aimed to study the determinants of hormonal contraceptive use and its effects among married women of reproductive age group in Kathmandu. This is a community based cross sectional study among 250 married women using hormonal contraceptives aged between 15-49 years residing in wards 8 and 9 of Gokarneshwor Municipality. The information was obtained using self-constructed structured questionnaire. Height, weight and blood pressure were recorded and hypertension was defined as per Joint National Committee (JNC) VII guidelines. Around one third of the participants were of 30-34 years and Depo-Provera was the most commonly used hormonal contraceptive. There were several side effects among the users and commonest were menstrual irregularities and weight gain. Around 47 participants had hypertension and 120 had raised BMI. The factors associated with hormonal contraceptive use were socioeconomic status, religion, BMI and monthly income of family of the study population. The present study provides valuable information regarding significant positive correlation of age, BMI and duration of hormonal contraceptive use with systolic and diastolic BP.